Rest Area Di Kecamatan Xiii Koto Kampar Km.99 Dengan Pendekatan Arsitektur Biofilik - Fikri, Habibul; Hidayat, Wahyu; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The West Sumatra - Riau causeway is an important line for the provinces of Riau and West Sumatra. The causeway has a role as an economic link between the two Provinces so that thelevel of road use is quite high and results in high intensity of accidents. Drowsiness is one of the causes of the high number of accidents on the West Sumatra - Riau crossroads, so users need a place to rest. Biophilic architecture has the function of accelerating the recovery of theuser's condition by getting the users closer to nature. Utilization of natural materials, scenery, and natural aromas can accelerate the recovery of the user's condition. Then the main problem is how to design a Rest Area by applying Biophilic Architecture, and there are 14principles in designing Biophilic Architecture.Keyword: Biophilic, Kec. XIII Koto Kampar, Rest Area